Switching mode circuit analysis and design : innovative methodology by novel solitary electromagnetic wave theory - Tohya, Hirokazu (Bentham Science Publishers, 2013)
Innovative Methodology by Novel Solitary Electromagnetic Wave Theory - The switching mode circuit (SMC) is being used in almost all electronics equipment. This e-book presents the theories and the technologies based on the novel solitary electromagnetic wave theory for the analysis and design of SMCs. This e-book presents the ultimate solution for the electromagnetic interference problems encountered while designing a switching mode circuit - including EMC, crosstalk, bounce, spike, and other signal integrity items.